An improved method of DNA extraction from plants for pathogen detection and genotyping by polymerase chain reaction - Sharma, K.; Bhattacharjee, Ranjana; Sartie, A.M.; Kumar, P. Lava (Academic Journals, 2013)
Polymerase chain reaction (PCR)-based applications in plant molecular biology and molecular diagnostics for plant pathogens require good quality DNA for reliable and reproducible results. Leaf tissue is often the choice for DNA extraction, but the use of other sources such as tubers, stems, or seeds, is not uncommon. The extraction of DNA from different tissue sources often requires different protocols. In this study, a simple protocol was established for the extraction of DNA from leaves, tubers, stems, seeds and even fungal mycelia. The protocol is simple and suitable for high-throughput DNA extraction using automated tissue grinders. It yielded large quantities of DNA (0.4 ?g to 2 mg DNA from 100 mg tissue) of high quality from seeds of maize, soybean, and cowpea, tubers of yam, tuberous roots of cassava, and leaf tissues of banana and plantain, yam, cassava, maize, okra, mango, and other species. DNA was successfully used for the detection of fungal and viral pathogens and the genotyping of yam and cassava by PCR.